Drug delivery as a sustainable avenue to future therapies - Fuhrmann, Gregor (Journal of Controlled Release, 2023)
Climate change and the need for sustainable, technological developments are the greatest challenges facing humanity in the coming decades. To address these issues, in 2015 the United Nations have established 17 Sustainable Development Goals. Anthropogenic climate change will not only affect everyone personally in the coming years, it will also reinforce the need to become more sustainable within drug delivery research. In 2021, I was appointed professor for pharmaceutical biology at the Friedrich-Alexander-University Erlangen-Nürnberg. Our research is at the interface between developing biogenic therapies and understanding of bacterial infections. In this contribution to the Orations – New Horizons of the Journal of Controlled Release, I would like to underline the need for future sustainable approaches in our research area, by highlighting selected examples from the fields of infection research, natural product characterisation and extracellular vesicles. My aim is to put into perspective current issues for these research topics, but also encourage our current student-training framework to contribute to education for sustainable development. This contribution is a personal statement to increase the overall awareness for sustainability challenges in drug delivery and beyond.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Academic publishing; Education for sustainable development; Extracellular vesicles; Infection research; Natural products; Sustainable development goals; Sustainable pharmacy